Magnetism and morphology in faceted B2-ordered FeRh nanoparticles. (2nd December 2016) - Liu, M.; Benzo, P.; Tang, H.; Castiella, M.; Warot-Fonrose, B.; Tarrat, N.; Gatel, C.; Respaud, M.; Morillo, J.; Casanove, M. J.
Abstract: Whereas the bulk equiatomic FeRh alloy with B 2 structure is antiferromagnetic (AFM) below 370 K, we demonstrate that the surface configuration can stabilize the low-temperature ferromagnetic (FM) state in FeRh nanoparticles in the 6–10 nm range. The most stable configuration for FM nanoparticles, predicted through first-principles calculations, is obtained in magnetron sputtering synthesized nanoparticles. The structure, morphology and Rh-(100) surface termination are confirmed by aberration-corrected (scanning) transmission electron microscopy. The FM magnetic state is verified by vibrating sample magnetometry experiments. This combined theoretical and experimental study emphasizes the strong interplay between surface configuration, morphology and magnetic state in magnetic nanoparticles.